Hedonism Before Bentham. (1st January 2015) - Moen, Ole Martin
Abstract : The hedonistic theories of Jeremy Bentham and John Stuart Mill are both widely known. Hedonism before Bentham, however, is much less known and, hitherto, no systematic presentation of hedonism's early history has been written. In this paper I seek to fill this gap in the literature by providing an overview of hedonism in early Indian and ancient Greek thought (Sections 1-4), in Roman and Medieval thought (Section 5), and from the Renaissance until the Enlightenment (Section 6).